2017
DOI: 10.13181/mji.v26i3.1873
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of magnetic resonance imaging in detecting anterior cruciate ligament injuries

Abstract: ABSTRAK ABSTRACTBackground: The anterior cruciate ligament (ACL) stabilizes the joint during hyperextension and prevents anterior translation over femur. The objective of this study was to determine the diagnostic accuracy of magnetic resonance imaging (MRI) in detecting ACL injury by taking arthroscopy as gold standard in patients with traumatic knee injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The most accurate and reliable sign of an ACL tear was the discontinuity of the ACL in both sagittal and axial planes. MRI has high accuracy for patients with complete ACL rupture according to Ahmad et al 17 A study by Khanda et al on 50 patients also showed the sensitivity of 86.67% for MRI in detecting ACL tears whereas our study has sensitivity values as high as 91.3% 18.…”
Section: Resultssupporting
confidence: 49%
“…The most accurate and reliable sign of an ACL tear was the discontinuity of the ACL in both sagittal and axial planes. MRI has high accuracy for patients with complete ACL rupture according to Ahmad et al 17 A study by Khanda et al on 50 patients also showed the sensitivity of 86.67% for MRI in detecting ACL tears whereas our study has sensitivity values as high as 91.3% 18.…”
Section: Resultssupporting
confidence: 49%